2012
DOI: 10.1016/j.abb.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of zinc in catalytic activity of carbonic anhydrase IX

Abstract: The carbonic anhydrases (CAs) in the α class are zinc-dependent metalloenzymes. Previous studies have reported that recombinant forms of carbonic anhydrase IX (CAIX), a membrane-bound form of CA expressed in solid tumors, appear to be activated by low levels of zinc independent of its well-studied role at the catalytic site. In this study, we sought to determine if CAIX is stimulated by zinc in its native environment. MDA-MB-231 breast cancer cells express CAIX in response to hypoxia. We compared CAIX activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Superoxide dismutase, a Zn-dependent enzyme, provides antioxidant defense for the placenta ( Mistry and Williams, 2011 ), which may have reduced activity during instances of pregnancy complications such as stillbirth in humans. Furthermore, Zn ions are present at the active site of carbonic anhydrase, which is necessary for transport and regulation of carbon dioxide ( Tu et al, 2012 ). Vallet et al (2014) hypothesized that additional Zn may increase carbonic anhydrase activity which may, in turn, build resistance to high CO 2 concentrations during birth, and potentially improve chance of survival for piglets that would otherwise be stillborn.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase, a Zn-dependent enzyme, provides antioxidant defense for the placenta ( Mistry and Williams, 2011 ), which may have reduced activity during instances of pregnancy complications such as stillbirth in humans. Furthermore, Zn ions are present at the active site of carbonic anhydrase, which is necessary for transport and regulation of carbon dioxide ( Tu et al, 2012 ). Vallet et al (2014) hypothesized that additional Zn may increase carbonic anhydrase activity which may, in turn, build resistance to high CO 2 concentrations during birth, and potentially improve chance of survival for piglets that would otherwise be stillborn.…”
Section: Resultsmentioning
confidence: 99%
“…Previously Frost and colleagues reported a K i value of 85.3 nM against extracellular CA for the fluorescent sulfonamide Cpd 5c in intact hypoxic MDA-MB-231 cells using the same 18 O exchange assay [ 31 ]. Extracellular CA activity of MDA-MB-231 cells was also significantly reduced by 1 μM acetazolamide [ 32 ]. The inhibitors VR16-09 and VD11-4-2 exhibited higher effect towards CA IX expressed in cellular models than previously reported compounds likely due to higher affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 illustrates several of the enzymes most recently identified as zinc metalloenzymes in the continuing elucidation of their extent and functions in nature [7,8,9]. Meanwhile, studies on the active site of carbonic anhydrase, the first of the zinc metalloenzymes identified, and its mode of operation continue to advance six decades later [10]. …”
Section: Organic Chemistry Of Zincmentioning
confidence: 99%